2019
DOI: 10.1002/stem.3088
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Stimulation of pediatric cardiac-derived c-kit+ progenitor cells improves retention and cardiac function in right ventricular heart failure

Abstract: Nearly 1 in every 120 children born has a congenital heart defect. Although surgical therapy has improved survival, many of these children go on to develop right ventricular heart failure (RVHF). The emergence of cardiovascular regenerative medicine as a potential therapeutic strategy for pediatric HF has provided new avenues for treatment with a focus on repairing or regenerating the diseased myocardium to restore cardiac function. Although primarily tried using adult cells and adult disease models, stem cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 60 publications
(85 reference statements)
1
4
0
Order By: Relevance
“…RV wall thickness during diastole (RVWT;d) was measured in the twodimensional short-axis view in M-mode. As previously shown, this surgery produces severe right ventricular dysfunction within two weeks post-banding (Maxwell et al, 2019;Trac et al, 2018). Right ventricular dysfunction was confirmed as at least a 40% reduction in TAPSE.…”
Section: Rat Pulmonary Artery Banding Modelsupporting
confidence: 67%
“…RV wall thickness during diastole (RVWT;d) was measured in the twodimensional short-axis view in M-mode. As previously shown, this surgery produces severe right ventricular dysfunction within two weeks post-banding (Maxwell et al, 2019;Trac et al, 2018). Right ventricular dysfunction was confirmed as at least a 40% reduction in TAPSE.…”
Section: Rat Pulmonary Artery Banding Modelsupporting
confidence: 67%
“…These reports include at least 19 studies in mice, 23 in rats, seven in pigs, and one in cats; 12 of these studies were done in animal models of old MI (chronic ischemic heart failure), and seven were performed in large animal (swine) models (Table 1). Except for four studies in models of isoproterenol-induced cardiomyopathy (Taghavi et al 2015), right ventricular injury by pulmonary artery banding (Maxwell et al 2019;Wehman et al 2017), and transverse aortic constriction (Kazakov et al 2015), all of these studies consistently show that administration of CPCs improved cardiac function after an acute, subacute, or old MI, often in association with a reduction in scar size, which in aggregate provides robust preclinical evidence of efficacy (Table 1). One study (Ellison et al 2013) used both a model of acute MI and isoproterenol-induced cardiomyopathy.…”
Section: Cpcs Are Effective In Preclinical Models Of Ischemic Cardiom...mentioning
confidence: 99%
“…In fact, a review of the literature demonstrates that there is extensive evidence from many other independent groups that administration of CPCs in preclinical models of ischemic cardiomyopathy (acute or old MI) is beneficial. As detailed in Table 1, at the time of this writing, at least 50 studies from 26 independent laboratories around the world have reported beneficial effects of CPCs in mice, rats, pigs, and cats (the 50 references are given in Table 1) (Alshammary et al 2013;Avolio et al 2015;Bao et al 2017;Bhutani et al 2018;Bolli et al 2013;Cai et al 2015;Carr et al 2011;Dergilev et al 2018;Duran et al 2013;Ellison et al 2013;Fischer et al 2009;Hong et al 2014;Kamata et al 2014;Karantalis et al 2015;Kazakov et al 2015;Kulandavelu et al 2016;Li et al 2017;Li et al 2011;Li et al 2012;Li et al 2018;Ma et al 2018aMa et al , 2018bMatsuda et al 2014;Maxwell et al 2019;Mohsin et al 2012;Natsumeda et al 2017;Oskouei et al 2012;Puddighinu et al 2018;Sharma et al 2015;Simpson et al 2012;Song et al 2016;Taghavi et al 2015;J.M. Tang et al 2015;X.L.…”
Section: Cpcs Are Effective In Preclinical Models Of Ischemic Cardiom...mentioning
confidence: 99%
“…There are also examples of the successful use of MSCs therapy in other areas of paediatrics, such as diabetes (9) , pulmonary and cardiac diseases (9,18,32,33) , reconstructive surgery and orthopaedy (9,34,35) , transplantation, and graft-versushost diseases (9,36) . One of the examples involves the successful treatment of diabetes mellitus in adolescents aged 14 to 22 years (9,37) with adipose-derived MSCs induced in vitro to produce insulin.…”
Section: Therapeutic Application Of Mscs In Paediatric Diseasesmentioning
confidence: 99%